Changing students' perceptions of the homeless: A community service learning experience. (March 2018) - Gardner, Janet; Emory, Jan
Abstract: The homeless are an underserved, local vulnerable population that can benefit from a service learning clinical practicum experience for baccalaureate prepared nursing students. Negative attitudes and disrespect among healthcare workers has been identified by the homeless as a barrier to healthcare. A service learning experience with a vulnerable population has been shown to change nursing students' attitudes and beliefs. A large university in a southern city partnered with a community based organization that provided services to the homeless to educate senior nursing students in a service learning experience. The goal of this project was to examine attitudes and perceptions of nursing students toward the homeless population before and after participation in a service learning clinical practicum experience. This case study utilized a pre and post experience questionnaire to collect qualitative data for the purposes of the project. The findings revealed students demonstrated a decrease in fear, an increase in empathy, and a deeper understanding of the advocacy role of nurses for people experiencing homelessness. Nurse educators are challenged to engage students with vulnerable populations to change the attitudes and perceptions for improvement in the overall health of communities served worldwide. Partnerships and service learning experiences can benefit all. Highlights: Community service learning experience with homeless affects nursing students' attitudes and perceptions. Community service learning experiences can bring awareness to students regarding vulnerable populations. Increases in empathy and positive changes in attitudes resulted from the community service learning experience for nursing students. Positive outcomes were consistent with those found in large metropolitan areas and rural communities.